2022
DOI: 10.1177/20414196221136157
|View full text |Cite
|
Sign up to set email alerts
|

A numerical investigation of blast-structure interaction effects on primary blast injury risk and the suitability of existing injury prediction methods

Abstract: Explosions increasingly occur in densely populated, urban locations. Primary blast injuries (PBIs), caused by exposure to blast wave overpressure, can be predicted using injury criteria, although many are based on idealised loading scenarios that do not necessarily reflect real life situations. At present, there is limited understanding of how, and to what extent, blast-structure interaction influences injury risk, and the suitability of injury criteria that assume idealised loading. This work employed computa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 35 publications
1
8
0
Order By: Relevance
“…Peak incident overpressure decreased with increasing distance around the corner, as expected due to the greater stand-off distances. However, an enhanced reduction was observed due to shielding from the corner structure compared to a free-field explosion without the structure, consistent with the findings of Denny et al [24]. This is similar to shielding observed from barriers used to mitigate blast effects on other buildings due to an external detonation [36,37] or clearing, which occurs on the reflected wall of a building and reduces the positive phase blast load [38].…”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…Peak incident overpressure decreased with increasing distance around the corner, as expected due to the greater stand-off distances. However, an enhanced reduction was observed due to shielding from the corner structure compared to a free-field explosion without the structure, consistent with the findings of Denny et al [24]. This is similar to shielding observed from barriers used to mitigate blast effects on other buildings due to an external detonation [36,37] or clearing, which occurs on the reflected wall of a building and reduces the positive phase blast load [38].…”
Section: Resultssupporting
confidence: 87%
“…A schematic and photograph of the field tests are shown in Figure 9. The charge mass and dimensions were also scaled using a factor of 250% when assuming a TNT equivalency of 1.2 for PE-4 [24]. The differences between the experiments herein and the field trials [11] exist:…”
Section: Numerical Modelling Results and Comparison To Experimental Workmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also clearly shown that numerical modelling can be utilised to provide verification at multiple stages of experimental work, further acting as a means to provide additional data in certain studies. Understanding the physical behaviours from experimental work can assist in validating numerical models; an example of this is given by the experimental work of Gajewski and Sielicki [164] being used to validate related modelling work conducted by Denny et al [165]. In this regard, the authors wish to highlight the importance of experimentalists publishing their collected data in full and in an accessible format, in order to facilitate rigorous and detailed validation of future modelling efforts.…”
Section: Methodsmentioning
confidence: 99%
“…In reality, blast wave interaction within Beirut's urban landscape will have modified the magnitude and distribution of loading conditions. Blast wave propagation in urban environments is complex to characterise and can both amplify and reduce loading through multiple reflections, channelling, and shadowing effects due to blast wave interactions with structures [21].…”
Section: Limitationsmentioning
confidence: 99%